Organic and mineral fertilizer field trial on rooibos tea under Northern Cape climatic conditions - Van Heerden, Stefanus Gerhardus (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.